The transcription factor CCAAT enhancer‐binding protein β protects rat cerebellar granule neurons from apoptosis through its transcription‐activating isoforms. (6th November 2013) - Peña‐Altamira, Emiliano; Polazzi, Elisabetta; Moretto, Edoardo; Lauriola, Mattia; Monti, Barbara
Abstract CCAAT enhancer‐binding protein β is a transcription factor that is involved in many brain processes, although its role in neuronal survival/death remains unclear. By using primary cultures of rat cerebellar granule neurons, we have shown here that CCAAT enhancer‐binding protein β is present as all of its isoforms: the transcriptional activators liver activator proteins 1 and 2, and the transcriptional inhibitor liver inhibitory protein. We have also shown that liver activator protein 1 undergoes post‐translational modifications, such as phosphorylation and sumoylation. These isoforms have different subcellular localizations, liver activator protein 2 being found in the cytosolic fraction only, liver inhibitory protein in the nucleus only, and liver activator protein 1 in both fractions. Through neuronal apoptosis induction by shifting mature cerebellar granule neurons to low‐potassium medium, we have demonstrated that nuclear liver activator protein 1 expression decreases and its phosphorylation disappears, whereas liver inhibitory protein levels increase in the nuclear fraction, suggesting a pro‐survival role for liver activator protein transcriptional activation and a pro‐apoptotic role for liver inhibitory protein transcriptional inhibition. To confirm this, we transfected cerebellar granule neurons with plasmids expressing liver activator protein 1, liver activator protein 2, or liver inhibitory protein respectively, and observed that both liver activator proteins, which increase CCAAT‐dependent transcription, but not liver inhibitory protein, counteracted apoptosis, thus demonstrating the pro‐survival role of liver activator proteins. These data significantly improve our current understanding of the role of CCAAT enhancer‐binding protein β in neuronal survival/apoptosis.